Curriculum Reform and Teaching Optimization of Computer Majors in the Intelligent Era - Hui, Danlan (Journal of Theory and Practice of Contemporary Education, 2024)
In the era of intelligence, also known as the Internet of Things, technological and industrial revolutions may occur in any country or corner at any time, and the key to these changes is the application of computer technology. Computer science is a national level discipline, which is highly valued by all sectors of society, Especially the setting and teaching mode of its professional courses are directly related to the strength of China's computer talent reserve. In this context, this article first analyzes the problems existing in China's computer professional education in the intelligent era, and then elaborates on its specific plans in curriculum reform and teaching optimization, hoping to be helpful for computer professional education work.